Kaji Eksperimen Limbah Cair Detergen Sebagai Sumber Energi Alternatif - Endri Yani; Sandri Kristian Dawolo (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
Detergent fluid waste is the useless product produced during the laundry process. Generally, the detergent waste is directly throw away to the water channel. In this research, the waste potential as the alternative energy is evaluated. Because of detergent is one of derivative product of crude oil, therefore it can be mixed with ash and charcoal and utilized as the electrolyte material for dry cell. In this research several types and composition of detergent waste such as solid, liquid and powder are analyzed. It was shown that the average voltage and the electric current produced by dry cell are 0.7 V - 0.8 V and 0.7 mA-1.3mA, respectively. The experiment results show that the higher of detergent concentrate, the larger electric current will be produced. Furthermore, using the same volume of electrolyte material, the battery using coconut shell mixed charcoal produces larger electric current than that using rice husk mixed charcoal.